3z+2(4x-2)=5(3-2)

Simple and best practice solution for 3z+2(4x-2)=5(3-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3z+2(4x-2)=5(3-2) equation:


Simplifying
3z + 2(4x + -2) = 5(3 + -2)

Reorder the terms:
3z + 2(-2 + 4x) = 5(3 + -2)
3z + (-2 * 2 + 4x * 2) = 5(3 + -2)
3z + (-4 + 8x) = 5(3 + -2)

Reorder the terms:
-4 + 8x + 3z = 5(3 + -2)

Combine like terms: 3 + -2 = 1
-4 + 8x + 3z = 5(1)

Multiply 5 * 1
-4 + 8x + 3z = 5

Solving
-4 + 8x + 3z = 5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 8x + 4 + 3z = 5 + 4

Reorder the terms:
-4 + 4 + 8x + 3z = 5 + 4

Combine like terms: -4 + 4 = 0
0 + 8x + 3z = 5 + 4
8x + 3z = 5 + 4

Combine like terms: 5 + 4 = 9
8x + 3z = 9

Add '-3z' to each side of the equation.
8x + 3z + -3z = 9 + -3z

Combine like terms: 3z + -3z = 0
8x + 0 = 9 + -3z
8x = 9 + -3z

Divide each side by '8'.
x = 1.125 + -0.375z

Simplifying
x = 1.125 + -0.375z

See similar equations:

| (8x^2-4x+14)+(-7x^2+3x-10)= | | 6x=2(4x+5) | | 3(4x+-5)=9 | | 3(4+-5)=9 | | 7c+-15=-2(6(c+-3)+-4(2+-1c)) | | 6x-3(2x-1)=6(-2+1)-3x | | 2x=180-7x | | 45=k(9)(5) | | -9p=-2 | | 4.9=7.3-0.6x | | a^2bc+ab^2c+abc^2=0 | | m^2+19m+48= | | X(x+81)=0 | | 8-2w^2=0 | | 5p-5q=-12 | | 4.9x+5=3.9x | | 10+8=-2(5x-9) | | 7x+9-6x=13 | | -20x=-4x-6 | | 2(x-3)=-h+3(h+6) | | 13-20= | | -14+1= | | v^2+2v-25=0 | | 2s^2=25 | | 150+110+450+x=1000 | | 4w+19=-7(w-9) | | X-6-25x^(1/2) | | 7+x+1=6x | | -14+26=-2(x+5) | | 7x-8(2x-3)=2(3x-9)-5x | | -10y+3y= | | 39+8p=-3(-5p-6) |

Equations solver categories